Žinių nuosavybės teisių apsauga verslo organizacijoje - Stonkienė, Marija (Information & Media, 2007)
Straipsnyje aptariama verslo organizacijos þiniø nuosavybës teisinës apsaugos sistema. Verslo organizacijos þinias suvokiant kaip nematerialius objektus, teigiama savita iðreikðtø þiniø nuosavybës apsaugos galimybë intelektinës nuosavybës teisës normomis. Ávertinus verslo organizacijos neiðreikðtø þiniø naudojimo teisinio reguliavimo galimybes, konstatuojama, kad konkurencijos teisës normomis ribojamas verslo organizacijos neiðreikðtø þiniø naudojimas, darbo teisës normomis numatoma galimybë kompensuoti darbdavio iðlaidas darbuotojo þiniø gausinimui, jei darbuotojas keièia darbo vietà. Straipsnyje teigiama, kad verslo organizacijos þiniø portfelio nuosavybës teisinës apsaugos sistemà sudaro ne tik intelektinës nuosavybës teisës normos, bet ir specialios konkurencijos ir darbo teisës normos. Remiantis Lietuvos teisës normø analize supaþindinama su verslo organizacijos neiðreikðtø þiniø sklaidos teisiniu reguliavimu.* Protection of knowledge property rights in business organizations Marija Stonkienë Summary The article presents the idea of protection of knowledge property rights in business organisations. The knowledge possessed by a business organisation is treated as an intangible object. It is maintained that the norms of protection of intellectual property are also applicable to the protection of the organisation’s explicit knowledge. The system of protection of intellectual property determines that only such explicit knowledge may be regarded as an object of intellectual property, which is defined as such in legal acts, which conforms to identification requirements and conditions of protection of intangible assets as set forth in legal acts. It is noted that the possibilities of protection of intellectual property are determined by the explicit knowledge of an organisation. Transfer of property rights related to tacit knowledge is impossible for a business organisation because of specific features of such knowledge. Legal regulation is aimed at the use of tacit knowledge of a business organisation or individual (organisation’s staff member), which has been produced out of the resources of this business organisation, and in the interests of this business organisation. The use of tacit knowledge in the interests of a business organisation is ensured by protection of trade secrets of the business organisation, thus limiting unfair competition of the personnel of a business organisation. The article maintains that the system of protection of the knowledge portfolio property rights of a business organisation embraces not only legal norms related to intellectual property but also special legal norms related to competition as well as to labour relations.